1990
DOI: 10.1111/j.1471-0528.1990.tb02546.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic changes in composition and volume of the breast during the menstrual cycle, measured by magnetic resonance imaging

Abstract: Summary. The volumes and spin‐lattice (T1) relaxation times of breast tissues and parenchymal water content were measured non‐invasively by magnetic resonance imaging (MRI) in eight healthy women during four to eight consecutive menstrual cycles. Total breast volume, and parenchymal volume, T1 relaxation time and water content were lowest between days 6 and 15. Between days 16 and 28, parenchymal volume, T1 relaxation time and water content rose sharply by 38·9%, 15·1% and 24·5%, respectively, and peaked afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
0
3

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(81 citation statements)
references
References 16 publications
4
74
0
3
Order By: Relevance
“…Our results show a 48.3% increase in Hb and 28.1% increase in water concentration during the luteal phase, changes that are consistent with the physiological effects caused by ovarian hormone fluctuations during the menstrual cycle. After ovulation, blood flow to the breast can increase by up to 50%; there is an increase in breast volume; and parenchymal water content changes by an average of 25% during the latter half cycle (24,25). Changes in scattering were 3-5% and not statistically significant.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Our results show a 48.3% increase in Hb and 28.1% increase in water concentration during the luteal phase, changes that are consistent with the physiological effects caused by ovarian hormone fluctuations during the menstrual cycle. After ovulation, blood flow to the breast can increase by up to 50%; there is an increase in breast volume; and parenchymal water content changes by an average of 25% during the latter half cycle (24,25). Changes in scattering were 3-5% and not statistically significant.…”
Section: Resultsmentioning
confidence: 92%
“…MRI studies further suggest that fluctuations in endogenous hormones may alter menstrual-cycle patterns and impact breast cancer risk (23)(24)(25)(26). In addition, the phase of the menstrual cycle has been shown to influence mammographic accuracy and survival rates after tumor resection (27,28).…”
mentioning
confidence: 99%
“…Several studies have shown that mammographic density has a small, but not statistically signifi cant, increase in the luteal phase compared with the follicular phase (23)(24)(25)(26). MR imaging has been used to evaluate the changes of breast tissue and water content within the menstrual cycle (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Most studies have focused on evaluation of the effect of different physiologic phases on parenchymal enhancements ( 9,10,13,15 ), which is an important concern for accurate diagnosis of breast lesions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the background tissue enhancements are lower in the follicular than in the luteal phase, and screening MR imaging is recommended to be performed during the follicular phase. Several studies have reported changes in breast tissue at MR imaging during a menstrual cycle (7)(8)(9)(10)(11)(12)(13)(14)(15)(16), including water and fat content ( 8 ), parenchymal enhancement ( 9,10,13,15 ), elasticity ( 11 ), water diffusion ( 12 ), breast volume (BV), and fi broglandular tissue volume (FV) ( 7,14,16 ).…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation